The Effect of Growth Regulator Formulation and Boron on The Growth and Yield of Shallot Varieties - Puji Harsono; Ade Widya Putri; Eddy Tri Haryanto; Gani Cahyo Handoyo (Agrosains : Jurnal Penelitian Agronomi, 2025)
Regulators (PGRs) are used to stimulate the development and growth of bulbs in order to produce a large number of bulbs. This study aims to identify the effect of PGRs and boron formulations that can increase the growth and yield of several variety of shallots. This research took place in the cultivation field of Ngringo Village, Jaten District, Karanganyar Regency from April-August 2023. The method used was a Complete Randomized Blok Design (CRBD) consisting of two factors with four replications. The first factor was PGRs and Boron formulation (without and with GA3 200 ppm+BAP 50 ppm+NAA 50 ppm+ IAA 300 ppm + 1500 ppm boron formulation). The second factor was variety (Bima Brebes, Maja Cipanas, Batu Ijo and Tajuk). Data were analyzed by F test with 95% confidence level followed by Duncan’s Multiple Range Test (DMRT) with 95% confidence level. The results showed that the application of PGRs formulations GA3 200 ppm + BAP 50 ppm + NAA 50 ppm +IAA 300 ppm + 1500 ppm boron on shallots of Tajuk varieties was able to increase number of leaves by 5 leaves and able to increase number of bulbs per clump of 3 bulbs compared to without the aplication of PGRs and boron formulations. The Tajuk variety provides the best growth in fresh weight of 16 g higher stalks and in the yield of fresh weight of bulbs per clump 23 g compared to the Batu Ijo variety. Shallots treated with 200 ppm GA3 + BAP 50 ppm + NAA 50 ppm +IAA 300 ppm + 1500 ppm boron have not shown an increase in growth and yield accros various shallot varieties.